The role of physical activity and heart rate variability for the control of work related stress - Tonello, Laís; Rodrigues, Fabio B.; Souza, Jeniffer W.; Campbell, Camen S.; Leicht, Anthony; Boullosa, Daniel A. (Frontiers in Physiology, 2014)
Physical activity (PA) and exercise are often used as tools to reduce stress and therefore the risk for developing cardiovascular diseases. Meanwhile, heart rate variability (HRV) has been utilised to assess both stress and PA or exercise influences. The objective of the present mini review was to examine the current literature in regards to workplace stress, PA/exercise and HRV to encourage further studies. We considered original articles from known databases (PubMed, ISI Web of Knowledge) over the last 10 years that examined these important factors. A total of 7 studies were identified with workplace stress strongly associated with reduced HRV in workers. Longitudinal workplace PA interventions may provide a means to improve worker stress levels and potentially cardiovascular risk with mechanisms still to be clarified. Future studies are recommended to identify the impact of PA, exercise and fitness on stress levels and HRV in workers and their subsequent influence on cardiovascular health.